Surgical treatment of odontogenic myxoma and facial deformity in the same procedure - Gabriela Mayrink; Anibal Henrique Barbosa Luna; Sergio Olate; Luciana Asprino; Marcio de Moraes (Wolters Kluwer Medknow Publications, 2013)
Odontogenic myxoma (OM) is an uncommon benign tumor with aggressive and invasive behavior. Predominant symptoms are usually slow and painless swelling, sometimes resulting in perforation of the cortical borders of the affected bone. In this paper, a case report of a patient with an OM on the right maxillary sinus and a vertical excess of maxilla will be presented. The treatment chosen was tumor resection in association with orthognathic surgery with biomodels assessment for surgical planning. A 3-year follow-up showed disease free and stability of the new position of maxilla. The international literature is evaluated to discuss this case report.